Histone H2B gene transcription during Xenopus early development requires functional cooperation between proteins bound to the CCAAT and octamer motifs. - Hinkley, C (1992)
The ubiquitously expressed transcription factor Oct-1 and several other members of the POU domain protein family bind to a site, termed the octamer motif, that functions in the promoter and enhancer regions of a variety of genes expressed under diverse conditions. An octamer motif present in a conserved histone H2B-specific promoter element is required for S-phase-specific transcription of mammalian histone H2B genes in cultured cells. We have previously shown that the octamer motif in a Xenopus histone H2B gene promoter was inactive in nondividing frog oocytes. Here we show that the octamer motif, in addition to regulatory elements (TATAA, CCAAT, and ATF motifs) that are active in oocytes, is required for maximal H2B gene transcription in developing frog embryos. Factors binding to each of the H2B upstream promoter elements are present in oocytes and increase slightly in abundance during early development. The activity of the H2B octamer motif in embryos is not specifically associated with increased binding by Oct-1 or the appearance of novel octamer-binding proteins but requires the presence of an intact CCAAT motif. Our results indicate that synergistic interactions among promoter-bound factors are important for octamer-dependent H2B transcription. We suggest that the activity of the H2B promoter is regulated primarily by changes in the interactions between proteins already bound to the promoter rather than by alterations in their intrinsic abilities to bind DNA.